Enhancing photodegradation of Methyl Orange by coupling piezo-phototronic effect and localized surface plasmon resonance. (April 2023) - Li, Jing; Xie, Guangzhong; Jiang, Jin; Liu, Yanyou; Chen, Chunxu; Li, Weixiong; Huang, Junlong; Luo, Xiaolan; Xu, Ming; Zhang, Qiuping; Yang, Min; Su, Yuanjie
Abstract: Piezo-potential promoted photocatalysis enables a scalable and high-efficiency dye decomposition by conjugating the photoexcitation and mechanical stimulus. However, its catalytic efficiency is significantly restricted by the limited quantum yield and piezoelectric activity of catalysts. Herein, a heterogeneous CdS-Au composite photocatalyst was synthesized via a facile water bath heating and reflux condensation method for organic pollutants degradation. The synergism between piezo-phototronic effect and localized surface plasmon resonance facilitates photon-generated carrier separation and internal quantum efficiency. The loading of Au nanoparticles remarkably modulates the morphologies, surface defect, effective optronics utilization and photocatalytic activities of CdS nanospheres. A 2.3 folds enhancement in the photodegradation of Methyl Orange (MO) was observed with the optimal 4 mol% Au loading. Furthermore, the impact of frequency and intensity of ultrasonication on the electrochemical impedance and photocatalytic activity was systematically investigated. This work offers a promising approach for harnessing noise or vibration for environmental remediation and opens up a new route for designing and developing high-performance piezo-photocatalyst. Graphical Abstract: ga1 Highlights: The synergism between surface plasma and piezo-phototronic effect was proposed. A 2.3 folds enhancement in degradation was attained by loading 4 mol% Au NPs. The impact of ultrasonic frequency and intensity on degradation was investigated. Photogenerated carrier separation and internal quantum efficiency were improved.